Vaciamiento y repetición: figuraciones del fin de una década - Isabel A. Quintana (Cuadernos LIRICO)
The present paper analyzes the Roberto Aizanberg´s work realized at the Di Tella Institute in 1969, Juan José Saer´s Cicatrices and the film El dependiente directed by Leonardo Favio. My approach seeks to observe in these works a poetics or aesthetic focused of the emptiness of the world. The insistent repetition of scenes, motifs, descriptions accompanies an oppressive, circular relation that does not move forward. In the context of a fruitful epoch in terms of artistic expressions, on the verge of the seventies, I inquire the languages that keep a distant relation with local movements and nurture themselves of the avantgardist experiences in Europe. Before the explosion of a wide range of artistic manifestations, as well as a complex political moment that culminates with the Cordobazo, these works reveal the folding and dismounting of the materials with which they work: words, image, space, time.